The Optimization of the Time-Cost Tradeoff Problem in Projects with Conditional Activities Using of the Multi-Objective Charged System Search Algorithm (SMOCSS) - Sharbatdar, M. K.; Talatahari, S.; Mousavi, M. R. (Journal of History Culture and Art Research, 2016)
Abstract The appropriate planning and scheduling for reaching the project goals in the most economical way is the very basic issue of the project management. As in each project, the project manager must determine the required activities for the implementation of the project and select the best option in the implementation of each of the activities, in a way that the least final cost and time of the project is achieved. Considering the number of activities and selecting options for each of the activities, usually the selection has not one unique solution, but it consists of a set of solutions that are not preferred to each other and are known as Pareto solutions. On the other hand, in some actual projects, there are activities that their implementation options depend on the implementation of the prerequisite activity and are not applicable using all the implementation options, and even in some cases the implementation or the non-implementation of some activities are also dependent on the prerequisite activity implementation. These projects can be introduced as conditional projects. Much researchs have been conducted for acquiring Pareto solution set, using different methods and algorithms, but in all the done tasks the time-cost optimization of conditional projects is not considered. Thus, in the present study the concept of conditional network is defined along with some practical examples, then an appropriate way to illustrate these networks and suitable time-cost formulation of these are presented. Finally, for some instances of conditional activity networks, conditional project time-cost optimization conducted multi-objectively using known meta-heuristic algorithms such as multi-objective genetic algorithm, multi-objective particle swarm algorithm and multi-objective charged system search algorithm.